CGIAR’s critical contribution to SDG 16 - a universe of untapped impacts, partnerships and resources - Läderach, Peter R.D.; Pacillo, Grazia; Osorio, Diego (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The development of CGIAR FOCUS Climate Security has revealed CGIAR’s untapped potential to contribute to SDG16 and the Humanitarian Development and Peace (HDP) nexus. Here we explain why CGIAR’s contribution is of such importance, and how it should articulate its contribution to SDG16 followed by specific comments on the One CGIAR strategy.